Impact of Digital Marketing on Business Performance of Small and Medium Businesses in Birendranagar, Surkhet - Dillu Prasad Dhungana (Journal of Nepalese Management and Research, 2024)
This study explored the impact of digital marketing on the business outcomes of small and micro enterprises in Birendranagar, Surkhet. Despite recognized benefits, local businesses faced significant barriers, including limited resources and technical expertise, necessitating a focused investigation within Birendranagar’s context. The study’s primary objectives were to evaluate digital marketing adoption, its impact on business performance, and the mediating role of customer engagement. Using descriptive and analytical research designs, data were collected from 167 businesses through surveys and interviews. The findings indicated moderate adoption of digital marketing, with social media, email, content marketing, and SEO being commonly used. Customer engagement, monitored through social media interactions and email tracking, played a crucial mediating role in enhancing business performance. Descriptive and inferential statistics, including correlation and regression analyses, revealed strong positive relationships between digital marketing strategies, customer engagement, and business performance. Specifically, digital marketing significantly improved revenue, customer acquisition, and profitability, with a Cronbach’s Alpha of 0.927 indicating high reliability of the measures used. The study concluded with recommendations to enhance digital marketing effectiveness, emphasizing the importance of technical training and strategic budget allocation. This research provided valuable insights for local entrepreneurs, helping them leverage digital tools to optimize business performance.